(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
Academic resilience is the ability to move forward amid the difficulties and challenges that are occurring, to strive and remain positively uplifted in facing the hardships at hand. One of the factors that can influence academic resilience is social support, which is the assistance received by individuals from those around them that can boost self-confidence and help them face their problems. The aim of this research is to examine the relationship between social support and academic resilience among students who are working on their thesis at Padang State University. This research method uses a quantitative research method with a sample size of 341. The data analysis method employs simple linear regression analysis. The research results indicate that social support contributes 12.6% to the academic resilience of final-year students who are working on their thesis. This finding shows that social support is a strong predictor of academic resilience, where the higher the social support received by students, the higher their level of academic resilien